2014
DOI: 10.1155/2014/709152
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Therapy in Dermatology: A Review

Abstract: Zinc, both in elemental or in its salt forms, has been used as a therapeutic modality for centuries. Topical preparations like zinc oxide, calamine, or zinc pyrithione have been in use as photoprotecting, soothing agents or as active ingredient of antidandruff shampoos. Its use has expanded manifold over the years for a number of dermatological conditions including infections (leishmaniasis, warts), inflammatory dermatoses (acne vulgaris, rosacea), pigmentary disorders (melasma), and neoplasias (basal cell car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
195
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(203 citation statements)
references
References 74 publications
0
195
0
8
Order By: Relevance
“…Acrodermatitis enteropathica, a rare disease characterized by impaired absorption of zinc, reveals the essential role of zinc in bone metabolism. Zinc deficiency, induced by the disease, gives rise to retarded and impaired bone growth [308]. Zinc supplementation has also been shown to favorably modulate bone turnover by stimulating osteoblast bone formation while inhibiting osteoclast differentiation.…”
Section: Zincmentioning
confidence: 99%
“…Acrodermatitis enteropathica, a rare disease characterized by impaired absorption of zinc, reveals the essential role of zinc in bone metabolism. Zinc deficiency, induced by the disease, gives rise to retarded and impaired bone growth [308]. Zinc supplementation has also been shown to favorably modulate bone turnover by stimulating osteoblast bone formation while inhibiting osteoclast differentiation.…”
Section: Zincmentioning
confidence: 99%
“…One of the examples of impaired wound healing is acrodermatitis enteropathica, caused by reduced Zn 2ϩ uptake in the small intestine and reduced serum Zn 2ϩ levels (2,3,5). Surgical patients undergoing total hip replacement procedures have impaired wound healing that correlates with lower levels of serum Zn 2ϩ (6,7).…”
mentioning
confidence: 99%
“…In this study, we found that 10 mg/kg/day zinc prevented IH-induced left ventricular dysfunction in rats. The recommended daily dosage of zinc for healthy individuals is 0.5 to 1 mg/kg/day in children and 15 to 30 mg/day in adults [76]. Whether these doses are sufficient for preventing cardiac injury in patients with OSA during high-intensity exercise needs further investigation.…”
Section: Discussionmentioning
confidence: 99%